COEXISTENCE OF STUNTING AND ANEMIA AMONG CHILDREN UNDER FIVE: PREVALENCE AND SHARED RISK FACTORS - Pratiwi, Dessy; M. Rajab, Nurfadilah; Aulia, Bianda; Larasati, Adisti Qamahadlina (Journal of Indonesian Specialized Nutrition, 2026)
Background: Stunting and anemia frequently co-occur in children under five, exacerbating undernutrition burdens in low- and middle-income countries (LMICs). This narrative review synthesizes evidence on the prevalence and shared risk factors of concurrent stunting and anemia in children under five. Methods: We searched three electronic databases: PubMed, Scopus, and Google Scholar and included studies published from January 2010 to December 2025. Search terms combined keywords related to “stunting”, “anemia”, “coexistence”, and “children under five”. Results: The coexistence of stunting and anemia affects approximately one in five children under five in LMICs with individual country estimates varied widely at 5.6–60.1%. Shared determinants included child age, small birth size, recurrent infections, inadequate dietary diversity and intake of animal‑source foods and legumes, maternal anemia, short stature, low maternal education, household poverty, open defecation, and limited access to quality health and water, sanitation and hygiene services. Conclusion: Evidence supports integrated, multi‑sectoral strategies that target maternal nutrition, infant and young child feeding, infection control, and environmental sanitation to reduce the coexistence of stunting and anemia in early childhood.